Knowledge Management as a Strategy for Attaining Quality in the Selected Petroleum Industries in the Middle East and North African (MENA) Region - Pineda, Aaron Paul M.; Maderazo, Marilou A.; Pineda, Rosalinda M.; Reyes, Faustino D. (Mediterranean Journal of Social Sciences, 2020)
As the world of business and industry advances toward interdisciplinary in the management of information and the utilization of the output of research and development, there is an increasing recognition of the importance of coordination in the promotion of quality in modern firms. The necessity of coordination has been brought about by the entry of massive data and information that have been generated by the various units of many business and industrial corporations.This study aimed to determine the extent to which knowledge management was used as a means toward the attainment of quality and the effects of knowledge management on the quality assurance views of a selected industrial petroleum industries in the Middle East and North African (MENA) Region in order to propose recommendations for enhancement. The researchers based this study on the theory advanced by Koenig (2012) who defined knowledge management as a discipline which promotes and integrated approach to the identification, retention, evaluation, retrieval, and sharing of all of the information assets of an enterprise. This research used assets such as data bases, documents, policies, procedures, and previous expertise and experiences of individual workers. The descriptive-survey method through the use of questionnaire as the instrument of data collection was used in this study. The descriptive study was used because the researchers intended to conduct a study of the actual situation in connection with knowledge management in the promotion of quality of operations in an industrial corporation. The extent to which knowledge management is used as a tool toward the attainment of quality in the selected industrial corporations in the MENA Region is of interest to the researchers. For this reason, this study was conducted.